Estilos de personalidad y estrategias de afrontamiento en pacientes diagnosticados con VIH-SIDA - Jacho Ruilova, Lissette Carolina (2018)
The present investigation has as purpose describe the strategies of confrontation used in patients diagnosed with HIV / AIDS according to his style of personality. The methods and techniques that were used for the next study was the qualitative and quantitative methodology taking as foundation the cognitive – behavorial approach, which is a holistic model that allows a more solid sustenance in this study, in addition, this allows a better understanding of the existing concatenation between personality styles and coping strategies in seropositive patients. The categories analyzed in this study were: personality styles and coping strategies. The selected cases were 6 seropositive patients of subsequent attention of the Type C Health Center Velasco Ibarra of the Machala city, which were taken without distinction of sex, age or sexual orientation. The research was carried out under the modality of mixed study (qualitative-quantitative). The design with which the work was done was narrative orientation, the method used was the biographical one because data collected by the patients were collected with the purpose of knowing their thoughts, ideas, emotions and feelings in front of the focus of the study. The techniques and instruments applied were. Deep interview in areas such as work and personal, family and social area, affective and sexual, Inventory of Personality Styles of Millon (DDMIPS) which measures different personality styles (introverted - withdrawn [asocial, passive and avoidant], inhibited - doubtful [avoidant, active - isolated], Cooperative [submissive, passive-dependent], sociable / extroverted [histrionic, active dependent], reliable / positive [narcissistic, passive- independent], strong and dissident [aggressive, active independent], controllers [aggressive, active discordant], respectful / conformist [passive conformist - ambivalent], sensitive / complaining [negativist, active - ambivalent], submissive [negativist, passive - discordant] ), Ways of Coping that measures three cognitive-behavioral and emotional coping strategies.